2011
DOI: 10.1007/s00421-011-2216-5
|View full text |Cite
|
Sign up to set email alerts
|

Muscular strength and markers of insulin resistance in European adolescents: the HELENA Study

Abstract: The aim of the study was to examine the association of muscular strength with markers of insulin resistance in European adolescents. The study comprised a total of 1,053 adolescents (499 males; 12.5-17.5 years) from ten European cities participating in the Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA) Cross-Sectional Study. Muscular strength was measured by the handgrip strength and standing long jump tests. Cardiorespiratory fitness was measured by the 20-m shuttle run test. Fasting insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
33
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 48 publications
5
33
0
3
Order By: Relevance
“…For ANCOVA, adiponectin levels were categorized into quartiles based on the distribution of adiponectin concentrations, and geometric mean values were used to test for linear trends in increasing quartiles. A secondary analysis was performed to evaluate the associations between serum adiponectin and muscle strength relative to body weight [22]. All statistical tests were twotailed; p values less than 0.05 were considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…For ANCOVA, adiponectin levels were categorized into quartiles based on the distribution of adiponectin concentrations, and geometric mean values were used to test for linear trends in increasing quartiles. A secondary analysis was performed to evaluate the associations between serum adiponectin and muscle strength relative to body weight [22]. All statistical tests were twotailed; p values less than 0.05 were considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…These associations (with exception of hip bone mass in boys and whole-body bone mass in girls) remained even after controlling for weight, height, pubertal stage, weight-bearing activities, and calcium intake (Chan et al, 2008). Other studies have shown positive associations between handgrip strength and cardiometabolic profiles and therefore suggest that muscle strength might have an important role in the prevention of both functional status and cardiovascular disease (Jimenez-Pavon et al, 2012;Ortega, Ruiz, Castillo, & Sjostrom, 2008).…”
mentioning
confidence: 88%
“…In addition, this organisation encourages engagement in regular bone-strengthening and muscle-strengthening activities on at least 3 days of the week 6 7. In the obese paediatric population, both aerobic exercise training (AT) and resistance exercise training (RT) improve low-density lipoprotein (LDL-C) and triglycerides (TG) concentrations,8 systolic blood pressure (SBP),9 flow-mediated dilation,10 fasting insulin and glucose,11 and body composition 12…”
Section: Introductionmentioning
confidence: 99%